Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1196/annals.1333.055
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Oral Maillard Reaction Product Load in the Form of Bread Crusts in Healthy and Subtotally Nephrectomized Rats

Abstract: The biological consequences of chronic consumption of Maillard reaction products (MRPs) on renal function in health and renal disease are still incompletely understood. We investigated the metabolic and renal effects of a diet with varying MRP content in healthy and subtotally nephrectomized rats. Male Wistar rats were subjected to sham operation (control, C, n = 12), or to 5/6 nephrectomy (5/6NX, n = 12). Both groups were randomized into subgroups and pair-fed with either a MRP-poor or -rich diet for six week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 26 publications
(36 reference statements)
3
39
0
12
Order By: Relevance
“…In spite of the fact that the metabolic transit data for the majority of ingested AGEs remain unknown, several lines of evidence suggest that an AGE-rich diet can lead, at least in susceptible individuals (such as infants, elderly and diseased people), to potentially pathologic consequencesbody and organ weight gain, obesity with metabolic syndrome [79, 84 -86], renal damage (via induction of proteinuria and/or enhanced formation of pro-fibrotic transforming growth factor b 1 (TGF-b 1 )) [79,84,85,87], accelerated atherosclerosis (via lipid peroxidation) [73,84], and lowdegree inflammation [74,88].…”
Section: Pathogenic Significance Of Dietary Agesmentioning
confidence: 99%
“…In spite of the fact that the metabolic transit data for the majority of ingested AGEs remain unknown, several lines of evidence suggest that an AGE-rich diet can lead, at least in susceptible individuals (such as infants, elderly and diseased people), to potentially pathologic consequencesbody and organ weight gain, obesity with metabolic syndrome [79, 84 -86], renal damage (via induction of proteinuria and/or enhanced formation of pro-fibrotic transforming growth factor b 1 (TGF-b 1 )) [79,84,85,87], accelerated atherosclerosis (via lipid peroxidation) [73,84], and lowdegree inflammation [74,88].…”
Section: Pathogenic Significance Of Dietary Agesmentioning
confidence: 99%
“…Recent studies showed that chronic AGE-rich standard diet feeding studies in animals showed an increase in body weight with no report on the change in adipose mass with elevated insulin resistance (14,64,65). Conversely, a long term of feeding study of mice with AGE-restricted standard diet resulted in reduced body weight gain with enhanced insulin sensitivity and life span at the end of the study (66).…”
Section: Journal Of Biological Chemistry 44503mentioning
confidence: 99%
“…Supporting this notion, a recent study demonstrated that mice fed a standard chow diet supplemented with 1 mg of MG-BSA/g of diet for 18 months showed elevated AGE levels in the serum as well as in adipose tissue to 0.43 mg of CML-BSA/ml and 190 nmol of MG/g of tissue, respectively (63). Collectively, these studies suggest that the AGE concentration we used in our study is likely to be achievable in the sera of humans and animals after a chronic oral administration of an AGE-rich diet.Recent studies showed that chronic AGE-rich standard diet feeding studies in animals showed an increase in body weight with no report on the change in adipose mass with elevated insulin resistance (14,64,65). Conversely, a long term of feeding study of mice with AGE-restricted standard diet resulted in reduced body weight gain with enhanced insulin sensitivity and life span at the end of the study (66).…”
mentioning
confidence: 99%
“…In der finalen Phase werden weitere heterocyclische Verbindungen gebildet und durch Polymerisation und Vernetzung ("crosslinking") dieser Verbindungen entstehen die niedermolekularen Prämelanoidine und die höhermolekularen Melanoidine (Krause, 2005;Somoza, 2005). Prämelanoidine und Melanoidine werden auch zusammenfassend als "fortgeschrittene Glykierungsprodukte" oder englisch als "Advanced Glycation Endproducts (AGEs)" bezeichnet (Bierhaus, 2004).…”
Section: Die Maillard-reaktionskaskadenunclassified
“…Die Bildungsmechanismen, die zur Entstehung der Vorstufen der Melanoidine führen, sind schon recht gut bekannt, aber über die nieder-und hochmolekularen Produkte der späteren Stadien der Maillard-Reaktion existieren bisher nur wenige Kenntnisse (Somoza, 2005). Die Struktur und die funktionellen Eigenschaften von Melanoidinen sind Gegenstand zahlreicher Forschungstätigkeiten (Krause, 2005).…”
Section: Die Maillard-reaktionskaskadenunclassified